Analisis Pengaruh Pelatihan Self-Leadership dan Motivasi Berprestasi terhadap Kinerja Kepala Desa di Kabupaten Gunung Kidul Yogyakarta - Muhamad Ali Sukrajap; Dewi Handayani Harahap (Universitas Proklamasi 45 Yogyakarta, 2017)
Ministry of Rural Regulation No. 6 Year 2014 about rural area said that the rural area has grown so it needs to be protected and empowered to be strong, advanced, independent, and democratic area, so as to create a strong foundation to implement governance and development towards a fair, affluent, and prosperous society. In fact, the equitable distribution of infrastructure and suprastructure is not evenly distributed in each village. This can be seen from the Rural Developing Index (IDM) stating the status of rural area development progress. Based on the IDM of Indonesia in 2015, that 45.57% (33,592 villages) were underdeveloped villages and 18.25% (13,453 villages) were very under-developed villages out of a total of 73,709 villages in Indonesia. The Village Head's job is to lead the administration of the Village Government. This study aims to determine the effect of Self-Leadership and Achievement Motivation Training on the Performance of Village Head in Gunung Kidul Regency of Yogyakarta Province. Based on the result of hypothesis testing by using Anova Repeated Measure, where the result shows that F = 11186,541 with significance level 0,000 (p <0,01), it proves that there is a very significant difference between pre-test, post-test, and follow-up.